Рання творчість Лесі Українки в літературно-критичній рецепції Івана Франка - Гуменюк, О.М. (Культура народов Причерноморья, 2014)
У статті розглядається насамперед ґрунтовна й доволі розгорнута праця Івана Франка
«Леся Українка» (1898), присвячена ранній творчості поетеси. Наголошується на неабиякому значенні
цієї праці в становленні поетичного хисту Лесі Українки, в історії української літературної критики.
Адже Іван Франко вказує на велику силу таланту юної поетеси, на той час авторки єдиної поетичної
збірки «На крилах пісень» та ще декількох поем, а також прозових п’єс. Мужнє слово Лесі Українки, на
думку І. Франка, гідно продовжує волелюбні шевченківські традиції. Притому критик вказує і на
неповторну ліричну пристрасність та проникливість, жіночну чарівливість поетичної манери авторки.
І. Франко підкреслює роль кримських вражень у формуванні художнього світу письменниці, в розвитку її
таланту, зазначає, що в циклі «Кримські спогади» її майстерність «засяяла повним блиском».
Разом з тим у статті звернено увагу на драматизм світосприймання І. Франка, який не відразу збагнув
деякі суттєві тенденції в творчості авторки, пов’язані з її виразним тяжінням до поетики модернізму. В статье рассматривается прежде всего обстоятельная работа Ивана Франко «Леся
Украинка» (1898), посвященная раннему творчеству поэтессы. Подчеркивается особое значение этой
работы в становлении поэтического мастерства Леси Украинки, в истории украинской литературной
критики. Иван Франко отмечает большую силу таланта юной поэтессы, в то время автора
единственного поэтического сборника «На крыльях песен», а также еще нескольких поэм и
прозаических драм. Приметно, что мужественное слово Леси Украинки, по мнению И. Франко,
достойно продолжает вольнолюбивые шевченковские традиции. При этом критик указывает и на
неповторимую лирическую страстность и проникновенность, женственное очарование
художественной манеры поэтессы. И. Франко ведет речь о роли крымских впечатлений в
формировании художественного мира писательницы, в развитии ее таланта, отмечает, что в цикле
«Крымские воспоминания» ее мастерство «засияло полным блеском».
Вместе с тем в статье обращается внимание на драматизм мировосприятия И. Франко, который не
сразу принял некоторые существенные тенденции в творчестве поэтессы, связанные с ее явственным
тяготением уже в раннем творчестве к поэтике модернизма. Prominent Ukrainian writer Ivan Franko is known not only as a poet, prose writer, playwright and
dramatist. His contribution to the development of the three main spheres of literature study - history, theory and
critics, is invaluable. The most bright piece of Franko’s literary-critical heritage include his rather detailed and
extensive work “Lesia Ukrainka” (1898), which is devoted to the early works of poetess. This Franko’s work is
examined in the first place in the article. Its special meaning is emphasized in formation of Lesya Ukrainka’s
poetical skills, in the history of the Ukrainian literacy criticism.
Ivan Franko marks the great power of the young poetess’s talent, at that time the sole writer of the poetic
collection “On the Wings of Songs”, several poems and also prosaic dramas. Conspicuously, in Ivan Franko’s
judgement, the courageous word of Lesya Ukrainka properly continues Shevchenko’s freedom-loving traditions
in Ukrainian literature. Critic also denotes the unique lyrical passion and emotion, feminine charm of the
poetesses manner. Ivan Franko tells about the great influence of the Crimean impressions on the poetess’s
artistic world, on the development of her talent. He also marks, that in the cycle “Crimean impressions” her
skills “began to shine with the full light”.
At the same time in the article the heed is given to dramatic effect on the world-view of Ivan Franko, who didn’t
accept right away some significant, related to Lesya Ukainka’s expressive inclination for the poetics of
modernism tendencies in her works.